A time-restricted feeding intervention in children and adolescents with obesity: The TRansForm study protocol - Molina-Giraldo, Paula; Murillo, Serafin; Meis, Laura; Sans, Oscar; Amat-Bou, Montse; Llobet, Marina; Jimenez-Chillaron, Josep C.; Ramon-Krauel, Marta; Lerin, Carles (Frontiers in Nutrition, 2022)
Obesity during childhood is of special concern as adiposity is typically tracked into adult life and it constitutes a major risk factor for future obesity and associated metabolic disorders. Recent studies indicate that time-restricted feeding (TRF) interventions may provide a promising strategy for obesity treatment. However, TRF interventions have only been tested in adult subjects. This study aims to determine both short- and long-term effects of a TRF intervention in children and adolescents with obesity. We will also investigate potential mechanisms mediating the response to the intervention, including the circadian rhythm and the gut microbiota composition. We have designed a randomized-controlled parallel-group clinical study in which children and adolescents (age range 8-18 year-old) with obesity will be subjected to time-restricted eating or no time restrictions for 2 months. Follow-up visits will allow for long-term effect assessments. We will measure anthropometric (BMI, adiposity) and metabolic parameters (glucose and lipid metabolism), circadian rhythm will be accurately monitored, and gut microbiota composition will be analyzed. This study will 1) determine safety and effectiveness of the TRF intervention in children and adolescents; 2) assess its long-term effects; and 3) evaluate potential mechanisms involved in the response to the intervention. This study is registered at ClinicalTrials.gov with ID NCT05174871